Designing a quantitative PCR assay for the detection of congenital Cytomegalovirus - Aaltoranta, Mikko (My University, 2021)
Human cytomegalovirus (CMV) is the most common cause of congenital infections worldwide. Congenital CMV (cCMV) infection is a significant cause of newborn morbidity and mortality and even an asymptomatic infection can cause long-term sequelae, most commonly sensorineural hearing loss. Universal screening is not currently performed for cCMV partially for the lack of suitable screening assays. The aim of this master’s thesis work is to develop a quantitative PCR (qPCR) assay for cCMV detection from dried blood samples (DBS). The qPCR was based on hydrolysis probes and seven commercial PCR master mixes were tested for the assay. Three different sample preparation methods were used: Prepito extraction where the CMV DNA was extracted from the DBS using a laborious DNA extraction kit, crude extraction where the DNA was extracted with one solution in a rapid cell lysis reaction and finally a direct protocol where a 1.5 mm DBS disc was used as a sample and the extraction step was combined with the qPCR’s temperature cycling. With direct samples, the CMV assay was able to detect 10/10 of CMV positive samples when the CMV concentration in blood was 10 000 IU/ml or higher and 8/10 when the concentration was 3 167 IU/ml. With 10 000 and 3 167 IU/ml CMV in blood, only 8 and 2.5 IU CMV, respectively, end up in the sample. Therefore, the assay can detect less than 10 IU/reaction using direct samples.